2001
DOI: 10.1086/322689
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of American Cutaneous Leishmaniasis with Miltefosine, an Oral Agent

Abstract: There is no recognized oral treatment for American cutaneous leishmaniasis. A rising-dose, open-label phase I/II trial of the oral agent miltefosine against Colombian cutaneous leishmaniasis was conducted. Seventy-two male Colombian soldiers (mean weight, 67 kg) received miltefosine at 50-100 mg/day for 3 weeks (for 32 evaluable patients) or at 133-150 mg/day for 3-4 weeks (for 32 evaluable patients). The per-protocol cure rate for 50-100 mg/day was 21 (66%) of 32 patients. The per-protocol cure rate for 133-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
2
10

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(126 citation statements)
references
References 16 publications
7
107
2
10
Order By: Relevance
“…Miltefosine was effective in curing patients with visceral leishmaniasis in India; however, few studies on the treatment of tegumentary leishmaniasis have been reported. In Colombia, a cure rate of 89-100% was observed for cutaneous leishmaniasis and was dependent on the dose used [86]; however, in general, the results in the New World are poor [87].…”
Section: Alternative Drugsmentioning
confidence: 99%
“…Miltefosine was effective in curing patients with visceral leishmaniasis in India; however, few studies on the treatment of tegumentary leishmaniasis have been reported. In Colombia, a cure rate of 89-100% was observed for cutaneous leishmaniasis and was dependent on the dose used [86]; however, in general, the results in the New World are poor [87].…”
Section: Alternative Drugsmentioning
confidence: 99%
“…In Colombia, two studies have been conducted for the treatment of CL. The first is a phase I-II study with a reported cure rate by protocol of 66% in individuals who received a dose of 50-100 mg/day and of 95% in individuals who received a dose of 133-150 mg/day 23 . The second study was a multicenter study (Colombia and Guatemala) where miltefosine was compared against a placebo; this study showed contradictory results.…”
Section: Introductionmentioning
confidence: 99%
“…The usual drugs used on leihsmaniasis therapy present several adverse effects as nephrotoxicity, hepatotoxicity and low efficacy (Soto et al, 2001). Besides the fractions F11 and F12 present activity against amastigota Leishmania (L.) amazonensis cells, they were not toxic to blood human cells.…”
Section: Discussionmentioning
confidence: 99%